Recent Developments in the Theory of Shells - Altenbach, Holm; Chróścielewski, Jacek; Eremeyev, Victor A.; Wiśniewski, Krzysztof (Advanced Structured Materials, 2019)
This book commemorates the 80th birthday of Prof. W. Pietraszkiewicz, a prominent specialist in the field of general shell theory. Reflecting Prof. Pietraszkiewicz's focus, the respective papers address a range of current problems in the theory of shells. In addition, they present other structural mechanics problems involving dimension-reduced models. Lastly, several applications are discussed, including material models for such dimension-reduced structures.